2001
DOI: 10.1002/pola.10006
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects on the polyethene chain structure of trimethylaluminum coordination to zirconocene catalysts

Abstract: Ethene was polymerized with the catalytic systems L2ZrCl2/MAO/TMA (where L = Cp, Me5Cp, or Me4Cp; Cp = η5‐cyclopentadienyl; MAO = methylaluminoxane; and TMA = trimethylaluminum) at 60 °C, 2 bar, and AlTMA/Zr ratios of 0–2700. The polymerization activity was reduced with the addition of TMA for L = Cp but was almost unaffected for the methyl‐substituted catalysts. Increasing the TMA concentration resulted in a lower molecular weight of the polymer, with the largest effect for L = Me5Cp. A gel permeation chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The signal at 3.53 ppm results from the presence of hydroxyl groups (-OH) in the polymer chain. This indicates that the alkylaluminium compound also participates in the termination reaction of the polymer chain [57,58]. Furthermore, intensity of this signal increases with the increase of the alkylaluminium activator concentration, which proves occurrence of this termination mechanism.…”
Section: Effects Of the Catalyst Recycling And Reaction Timementioning
confidence: 64%
“…The signal at 3.53 ppm results from the presence of hydroxyl groups (-OH) in the polymer chain. This indicates that the alkylaluminium compound also participates in the termination reaction of the polymer chain [57,58]. Furthermore, intensity of this signal increases with the increase of the alkylaluminium activator concentration, which proves occurrence of this termination mechanism.…”
Section: Effects Of the Catalyst Recycling And Reaction Timementioning
confidence: 64%
“…Assuming insignificant chain transfer to MAO, the degree of polymerisation for metallocene catalysts (M n ) can be described by the following equation: [11,24] …”
Section: Molecular Weightmentioning
confidence: 99%
“…Even though some TMA is practically always present in metallocene polymerisations activated by MAO, the role of TMA in the activation process and the effect of TMA concentration on catalyst activity often get little attention and it is not well understood. Lately Liu et al [11,12] reported that the effect of TMA on polymerisation behaviour is dependent on the structure of the metallocene precursor in ethylene polymerisations.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies through detailed polymer chain structure characterization have made important achievements . Studies on the polymerization kinetics have been conducted by more research groups for understanding the mechainsm . It is evident that kinetic studies based on direct measurement of the active center concentration in the polymerization system can lead to easier construction of a comprehensive mechanistic model.…”
Section: Introductionmentioning
confidence: 99%